0
$\begingroup$

$$x^6 - 4x^5 - 11x^4 + 40x^3 + 11x^2 - 4x - 1 = 0$$ and given root is $\sqrt{2} - \sqrt{3}$.

I tend to solve equations if the first given root number is not a $\sqrt{2}$ which in this case is. I understand this might be the dumbest question, nevertheless learning shouldn't stop.

Looking forward for help.

$\endgroup$
  • 2
    $\begingroup$ If $x$ is a root, $\frac{1}{x}$ is also a root. $\endgroup$ – Jack Tiger Lam Aug 25 '16 at 2:57
  • 3
    $\begingroup$ There are $4$ obvious roots to work with: $\pm \sqrt2\pm\sqrt3$. $\endgroup$ – Batominovski Aug 25 '16 at 2:58
4
$\begingroup$

Without much calculation, you know that $\pm \sqrt{2}\pm\sqrt{3}$ are four roots of this polynomial. Their sum is $0$ and their product is $1$. Hence, the two remaining roots must sum to $4$ and have $-1$ as their product.


Suppose we do not know beforehand that $\sqrt{2}-\sqrt{3}$ is a root of $$P(x):=x^6-4x^5-11x^4+40x^3+11x^2-4x-1\,.$$ We can find the roots of this polynomial in the following manner. Observe that $$P(x)=-x^6\,P\left(-\frac{1}{x}\right)\,.$$ Due to this symmetry, let $y:=x-\frac{1}{x}$ (I think Jack Lam wanted to point out this symmetry, but his hint is a bit off, namely, if $x=z$ is a root of $P(x)$, then $z\neq 0$ and $x=-\frac{1}{z}$ is also a root). Then, $$\frac{1}{x^3}\,P(x)=\left(x^3-\frac{1}{x^3}\right)-4\left(x^2+\frac{1}{x^2}\right)-11\left(x-\frac{1}{x}\right)+40\,.$$ Hence, $$\begin{align}\frac{1}{x^3}\,P(x)&=\left(y^3+3y\right)-4\left(y^2+2\right)-11y+40 \\ &=y^3-4y^2-8y+32=(y-4)\left(y^2-8\right) \\ &=(y-4)(y-2\sqrt{2})(y+2\sqrt{2})\,. \end{align}$$ That is, $$\begin{align} P(x)&=x^3\,(y-4)(y-2\sqrt{2})(y+2\sqrt{2})=\left(x^2-4x-1\right)\left(x^2-2\sqrt{2}x-1\right)\left(x^2+2\sqrt{2}x-1\right) \\ &=(x-2-\sqrt{5})(x-2+\sqrt{5})(x-\sqrt{2}-\sqrt{3})(x-\sqrt{2}+\sqrt{3})(x+\sqrt{2}-\sqrt{3})(x+\sqrt{2}+\sqrt{3})\,. \end{align}$$

$\endgroup$
  • 1
    $\begingroup$ Very slick and fine indeed. $\endgroup$ – Lubin Aug 25 '16 at 4:08
0
$\begingroup$

if $\sqrt2 - \sqrt 3$ is a root. And since our polynomial has rational coefficients... we know that the conjugates will also be roots.

$(x-\sqrt2 - \sqrt 3)(x-\sqrt2 + \sqrt 3)(x+\sqrt2 - \sqrt 3)(x+\sqrt2 + \sqrt 3)\\ (x^2-2\sqrt2x -1)(x^2+2\sqrt2x - 1)\\ x^4 - 10x^2 + 1$

$\dfrac {x^6 - 4x^5 - 11x^4 + 40x^3 + 11x^2 - 4x - 1}{x^4 - 10x^2 + 1}$

$x^2(x^4 - 10x^2 + 1)-4x(x^4 - 10x^2 + 1) - (x^4 - 10x^2 + 1)\\ (x^2 - 4x - 1)(x^4 - 10x^2 + 1)$

So your last two roots are $(2+\sqrt5), (2-\sqrt 5)$

$\endgroup$
0
$\begingroup$

\begin{align} &x=\sqrt2-\sqrt3\\ &x+\sqrt3=\sqrt2\\ &x^2+2\sqrt3x+3=2\\ &x^2+1=-2\sqrt3x\\ &x^4+2x^2+1=12x^2\\ &x^4-10x^2+1=0\\ &(x^4-10x^2+1)(x^2+ax-1)=x^6-4x^5-11x^4+40x^3+11x^2-4x-1\\ &=x^6+ax^5-11x^4-10ax^3+11x^2+ax-1\\ &\therefore a=-4\\ \\ &x^4-10x^2+1=0\rightarrow x=\pm\sqrt{5\pm2\sqrt6}=\pm\sqrt2\pm\sqrt3\\ &x^2-4x-1=0\rightarrow x=2\pm\sqrt5 \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.